Curva de maturação, tamanho de primeira maturação gonadal e fecundidade de Astyanax bimaculatus e Astyanax fasciatus da Represa do Lobo, estado de São Paulo (Osteichtyes, Characidae) - Barbieri, Geraldo; Cruz Barbieri, Marilene (Revista Ceres, 2025)
Aspects of the reproduction of Astyanax bimaculatus and A. fasciatus in the Lobo Reservoir (Sao Paulo State), were investigated during the period of one year.